HOW COULD THE BUYERS BE ENTHUSIASTIC TOWARDS THE PRODUCTS OF BAGUS DISCOVERY MANAGEMENT COMPANY?: WINNING MARKET SEGMENT IN BBTF - Gede Ginaya; I Gede Mudana; Ni Nyoman Sri Astuti; Nyoman Mastiani Nadra; Ni Made Rai Sukmawati (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2018)
Bali beyond Travel Fair (BBTF) is an annual national tourism agenda as a business-to-business event for local travel industry players to sell travel packages to foreign buyers. As one of the sellers in the annual event, Bagus Discovery Management Company (BDMC) that manage Nusa Dua Bali Tours & Travel, Puri Bagus Hotel Group, and Bagus Agro had participated actively in BBTF by opening a booth stand in Nusa Dua Hall of Bali Nusa Dua Convention Center as the event venue from June 27 to June 30. This study investigated the role of BDMC in BBTF through the writer’s direct practices when was involved in handling the event by conducting surveys in the fifth edition of BBTF. Additionally, interviews were conducted to the staff and top management of the company about the winning strategy for attracting buyers in such a potential marketing event as well as to buyers by asking their perception about the event. The data that had been classified then analyzed using descriptive qualitative based on inductive methodological paradigm by setting up the discussion from specifically principles to general before drawing a conclusion. The study reveals that most of the sellers who visited Bagus Discovery Booth Stand felt satisfied towards the service received and appreciated highly its products like Puri Bagus Group Property which is considered to possess a distinctive uniqueness as what certainly every guest is looking for